Characterization of micro- and nano- modified cementitious system using micro analytical techniques. (April 2015) - Hemalatha, T.; Gunavadhi, M.; Bhuvaneshwari, B.; Sasmal, Saptarshi; Iyer, Nagesh R.
Abstract: The influence of incorporation of micro and nano sized particles such as fly ash, silica fume, nanosilica and nanoalumina on the hydrated cementitious system is studied. The transformation in the hydrated products due to these additions are analyzed using X ray diffraction and scanning electron microscopy. Further, transition in the pore structure owing to the formation of hydrated products are evaluated through nitrogen adsorption/desorption (NAD) technique method and image analysis. The pore structure is characterized by the total pore volume and pore size distribution using NAD method and pore area fraction from image analysis. It is found that the micro and nano additions do not always improve the microstructure by reducing the pores, sometimes (in case of addition of nano materials/silica fume) increase the size of the pores by pore widening phenomena. Neverthless, it is realized that the nano alumina addition helps in filling the pores only at later ages.